Potensi Lulusan Perguruan Tinggi Keagamaan Hindu Institut Agama Hindu Negeri Gde Pudja Mataram Dalam Menghadapi Persaingan Kerja - Prajawati, Yani Timor; Oka, A.A Gde; Wibawa, I Gede Jaya Satria (Yayasan Alpatih Harapan Semesta, 2023)
National Development in the current era of digitalization and modernity, requires quality and capable human resources to apply and develop science and technology, including in the field of Education and pure science at IAHN Gde Pudja Mataram, paying special attention to Graduates from Religious Colleges Hindu. This special attention is in line with the statute of IAHN Gde Pudja Mataram, that the Main Scientific Pattern (PIP) of IAHN Gde Pudja Mataram, is religion and culture that color and become the scientific identity of graduates from IHN Gde Pudja Mataram. The competence and ethics of IAHN Gde Pudja Mataram graduates are expected to have mastery of science including theory and concept skills, method and analysis skills, synthesis skills based on their particular study program. Thus graduates are ready to compete in the world of work and the industrial world because they have potential within themselves. The independent learning program is a strategy that can be carried out in order to prepare competent graduates, therefore the focus of the problem raised in this study is to find out what obstacles graduates experience in facing competition in the world of work and industry, by reviewing the relevance of the eyes study at PTKH and prepare an effective strategy to produce competent graduates